La voz del silencio. Me llama desde siempre - Martinengo, Mariri (DUODA: estudis de la diferència sexual, 2011)
Memory and history of a woman deprived of one and the other: this could be the summary of the book; the book, in fact, was born of a desire that is –at the same time– the fulfilment of a promise, tacit, but no less binding: that the narration of the human history of the central character awakens in its descendants the debt of gratitude towards Ella and restores to her the loving memory that she has lacked. The path taken by the narration starts with the work on herself carried out by the author; it is developed through the disinterment and recomposing of memories, it meanders around the character’s life stages, articulated and revitalised through images, and then takes its time with the historical reconstruction of atmospheres, places, customs, mentalities of the period, in such a way that, together with the central figure, familial and social silhouettes take on form, on a background that throws into relief innovative historiographical profiles.